Rethinking Brechtian film theory and cinema - Koutsourakis, Angelos (Edinburgh University Press, 2018)
Making a compelling argument for the continuing relevance of Brechtian film theory and cinema, this book offers new research and analysis of Brecht the film and media theorist, placing his scattered writings on the subject within the lively film theory debates that took place in Europe between the 1920sÃǾ²ƠÂ₀1960s.